A systematic literature review exploring uncertainty management and sustainability outcomes in circular supply chains. Issue 19 (2nd October 2022) - de Lima, Felipe Alexandre; Seuring, Stefan; Sauer, Philipp C.
Abstract : The circular economy (CE) has inspired the emergence of circular supply chains (CSCs) to reduce the environmental impacts of linear production systems. However, the transition to CSCs faces numerous challenges and uncertainties, which in turn impact the sustainability performance of CSCs. Following a systematic review process, this paper aims to identify the uncertainties that CSCs entail and the uncertainty management strategies which can be used to mitigate them to enhance their sustainability performance. A conceptual framework is proposed under which the current literature on CSCs, including 106 peer-reviewed English journal articles, is analysed and discussed based on CE practices, uncertainty management, and sustainability performance indicators. This framework offers guidance to CE and CSC scholars and supports practitioners and policymakers in being aware of the uncertainties related to the operationalisation and implementation of the CE in order to offer CE-inspired solutions. This paper also proposes a research agenda to investigate the integration of CE practices with supply chain management; the ways in which organisations manage different uncertainties simultaneously; and the effect of multiple uncertainty management strategies on firms' sustainability performance.